1977
DOI: 10.1128/jb.130.3.1357-1363.1977
|View full text |Cite
|
Sign up to set email alerts
|

Methanococcus vannielii: ultrastructure and sensitivity to detergents and antibiotics

Abstract: Methanococcus vannielii is a strictly anaerobic motile coccus that possesses a tuft of flagellae. The cells are markedly sensitive to mechanical stress and are readily lysed by detergents, but the organism grows normally in media of low ionic strength. The absence of a typical cell wall, further suggested by resistance of M. vannielii to penicillin, cycloserine, and vancomycin, was confirmed by ultrastructural studies. Electron micrographs showed that the cell envelope lacks a peptidoglycan layer. On the outer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(31 citation statements)
references
References 17 publications
2
29
0
Order By: Relevance
“…The aminoglycoside-related antibiotics spectinomycin and kasugamycin, the macrolide antibiotics oleandomycin and erythromycin and lincomycin showed either no inhibition of growth or at high concentrations only. Chloramphenicol, as already reported [5,6] displayed intermediate to high effectivity on all archaebacteria tested.…”
Section: Resultssupporting
confidence: 84%
“…The aminoglycoside-related antibiotics spectinomycin and kasugamycin, the macrolide antibiotics oleandomycin and erythromycin and lincomycin showed either no inhibition of growth or at high concentrations only. Chloramphenicol, as already reported [5,6] displayed intermediate to high effectivity on all archaebacteria tested.…”
Section: Resultssupporting
confidence: 84%
“…were not uncoupled) in these cultures. Although little systematic work on the effects of detergents on methanogenesis has been accomplished, Jones et al [9] observed that the addition of 10 ppm sodium dodecyl sulphate to cultures of Methanococcus vannielii caused immediate cell lysis. The addition of SDBS at concentrations greater than 15 ppm to the M. barkeri cultures in the present study, revealed evidence of cell surface damage on scanning electron microscopical examination.…”
Section: Discussionmentioning
confidence: 99%
“…Data have also been reported concerning the effect it has on cell membrane permeability (Hancock & Fitz-James, 1964) and selective inhibition of ribonucleic acid synthesis (Jordan & Mallory, 1964). (Kandler & König, 1978), M. smithii (Dermoumi & Ansorg, 2001), or M. vannielii (Jones et al, 1977). The order of the attached amino acids is different in the case of pseudomurein cross-linking in comparison with murein.…”
Section: Vancomycinmentioning
confidence: 99%
“…This binding leads to the formation of a complex which prevents the conversion to the phosphate form leading to inhibition of peptidoglycan biosynthesis (Reynolds, 1971;Siewert & Strominger, 1967;Stone & Strominger, 1972;Storm & Strominger, 1973;Toscano & Storm, 1982;Weinberg, 1958Weinberg, , 1967 Bacitracin was tested against Methanococcus vannielii (Jones, Bowers, & Stadtman, 1977) (Hammes, Winter, & Kandler, 1979). Results show that bacitracin inhibited the activity of M. vanniellii and the four of the strains of the genus of Methanobacterium.…”
Section: Bacitracinmentioning
confidence: 99%
See 1 more Smart Citation